IMPLEMENTASI ACCOUNTING TREATMENT UNTUK MENGURANGI KERUGIAN AKIBAT RISIKO YANG DIHADAPI PERUSAHAAN - Elizabeth Tiur Manurung (Center for Economic Studies Universitas Katolik Parahyangan, 2009)
Risk as an uncertainties arise from unexpected events in a business world, such as upheavals in its political or economic environment (Reilly et.Al: ). Especially for lndonesia as a country with high population, although has rich and abundant natural resources, but in the contrary until now hasn't been able to escape from the impact of country risk. Moreover the condition recently which many natural disaster are more often to occur. The impact of those risks that carried on by the world of business is commonly come in a form of financial distress. This financial distress is generated from many aspects such as decline of liquidity, rise of cost of products, rise in liabilities that still must be paid, and advancement in working capital requirement. In the same time, the quantity of goods for sale declines as customers have also financial and payment difficulties. In turn, the company's/accounting profit will decline as well. In the last part of this article, some strategic are suggested to raise profit company's profit by hedging, insurance, input substitution, developing internal business process, product pricing strategy, improve the products quality, and also improvement of service to customers.